Il coinvolgimento drammaturgico e sensoriale dello spettatore negli spettacoli del Teatro del Lemming (Itinera, 2017)
Teatro del Lemming Company works since almost thirty years around the dramaturgical and sensorial involvement of the spectator. The first sensorial dramaturgy of Teatro del Lemming is Oedipus. Tragedy of senses for one spectator. The spectacle had its première in 1997. This piece breaks the mirror of the representation: the spectator sinks inside the dramaturgy with all his five senses. The spectator is blindfolded and has the protagonist’s role. He is led to re-experience on his body all landmarks of Oedipus’ myth. Certainly the condition of being blind creates a greater openness of the other senses. After Oedipus, the sensorial and dramaturgical involvement of the audience has become the particular sign of Teatro del Lemming’s theatrical productions.